(untitled) (Biological Sciences - PJSIR, 2008)
The study of the industrial potentials of the palm weevil revealed the water absorption capacity to range from 53.33% in the late larval stage (LLS) to 113.33% in adult stage (ADS) while oil absorption capacity varied from 87.97% in LLS to 121.33% in ADS. The adult had the highest emulsion capacity while none of the samples formed foams. ADS gelled at 4% while LLS and ELS (early larval stage) gelled at 10% and 16%, respectively. The oil had a specific gravity of 0.8742. Iodine and unsaponifiable matter were the highest in ELS, while LLS had the highest saponification value. ADS recorded the highest values for acid, free fatty acid, peroxide, slip point, melting point, softening point, smoke point, flash point and fire point. The anti-nutrient contents were generally low. Phytic acid was the highest in LLS, whereas, ADS had the highest oxalate and tannin contents.